The Perils of Sterilization. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
The paper argues that the sterilization of capital inflows at the start of a price-stabilization program may give rise to future pressures to discontinue the program as a result of the unduly high debt-service burden that the sterilization policy may generate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet